Fractional Evolution Equations and Applications - Henriquez-Miranda, H (John Wiley and Sons Ltd, 2018)
This work addresses the study of the Lp-boundedness and compactness of abstract linear and nonlinear fractional integro-differential equations. The analysis is performed for the whole range of values of p, ie, 1≤p≤+∞In addition, theoretical results are complemented with illustrating particular cases of systems modeled by fractional evolution equations as heat conduction problems and problems arising in the theory of viscoelastic materials. Copyright © 2017 John Wiley & Sons, Ltd.